Integrative Approaches to the Undergraduate Public Health Major Curriculum: Strengths, Challenges, and Examples - Kiviniemi, Marc T.; Przybyla, Sarahmona M. (Frontiers in Public Health, 2019)
Many “first generation” undergraduate public health majors were designed based on “siloed” course structures centered around subunits in the discipline (e.g., Introduction to Epidemiology, Introduction to Environmental Health) that may be meaningful primarily to experts in the field. An alternative to the siloed approach is an integrative curricular design, in which courses are designed around meaningful thematic units (e.g., explaining public health problems, asking and answering scientific questions in public health), with an emphasis on drawing connections between knowledge from different but complementary disciplinary areas as a means to improve student learning and retention. The integrative approach shifts the curriculum conversation to capitalize on the interdisciplinary roots of the public health profession. This approach is consistent with the learning outcome recommendations in the Framing the Future Task Force report and in the CEPH requirements for the undergraduate public health major. We explore integrative approaches to developing curriculum models for undergraduate public health programs and discuss both pedagogical and career preparation arguments supporting an integrative curriculum approach. These include facilitating the often-challenging task for students of seeing how concepts interrelate, making transparent how “basic” knowledge in the discipline relates to “real world” applications of the content, and better mirroring how professionals in the discipline actually use knowledge in practice. Finally, we review examples of core concepts and features in an integrative curriculum approach to the undergraduate public health major as an effective educational program with high-quality, learner-centered educational experiences.